Understanding the Veil According to Hadith: A Systematic Qualitative Study - Intan Pujiani; Taufik Rahman (Gunung Djati Conference Series, 2021)
This study aims to discuss the understanding of the veil according to the hadith. This research method uses a qualitative approach through literature study. The results and discussion of this study show that there is no strict hadith evidence that requires Muslim women to wear the veil. However, there are some hadiths that suggest that covering oneself is a habit of a female friend who is the best example. This study concludes that the use of the veil depends on the user's perception and interpretation of the hadith text. This research is expected to provide benefits and uses, especially for the enrichment of the treasures of Islamic knowledge.